PERAN PENDIDIKAN AGAMA DALAM MEMPERSIAPKAN GENERASI MUDA MENGHADAPI TANGGUNG JAWAB KELUARGA MENURUT HUKUM KELUARGA ISLAM: STUDI KASUS DI KADUHEJO PANDEGLANG - Nurhakim, Muhamad Syara; Hayati, Ela Hikmah; Inayatulloh, Siti; Fadia Rohmah, Putri (Ta'dibiya, 2022)
This research aims to explore the role of religious education in preparing the younger generation to face family responsibilities according to Islamic family law. The main focus of this research is on the Kaduhejo community, Pandeglang. The research method used is a qualitative method with data collection techniques through in-depth interviews, observation and document analysis. The research results show that religious education plays an important role in shaping the understanding and readiness of the younger generation to face family responsibilities. Religious education not only provides knowledge about Islamic teachings, but also involves moral and ethical values ​​that underlie family responsibilities in the context of Islamic family law. Respondents emphasized that a deep understanding of religious teachings helps them make decisions that are in line with Islamic values ​​in the context of marriage, parenting and family relationships.